Origins and consequences of child labor restrictions: a macroeconomic perspective - Matthias Doepke; Dirk Krueger (Institute for the Study of Labor (IZA), 2007)
We investigate the positive and normative consequences of child-labor restrictions for economic aggregates and welfare. We argue that even though the laissez-faire outcome may be inefficient, there are usually better policies to cure these inefficiencies than the imposition of a child-labor ban. Given this finding, we investigate the potential political-economic reasons behind the emergence and persistence of child-labor legislation. Our investigation is based on a structural dynamic general equilibrium model that provides a coherent and uniform framework for our analysis.
Keywords: I28; 330; Child labor; education; labor restrictions; Kinderarbeit; Regulierung; Arbeitnehmerschutz; Wohlfahrtseffekt; Makroökonomischer Einfluss; Theorie